LEGAL ANALYSIS OF BUYING AND SELLING DROPSHIP SYSTEM GRAIN IN MADIUN REGENCY(Verdict Study PN: No. 128/Pid.B/2022/PN Mjy) - Andika Risa Kurniawan; Haniyah (INTELIGENSIA MEDIA, 2024)
In the dropship system, sales have many advantages and disadvantages in buying and selling transactions. In buying and selling, the drop ship system also causes legal problems, namely dishonest sellers, sellers who do not send goods, drop shippers who do not pay off debts to suppliers for various reasons, inaccuracy in delivery times that are as agreed, and so on. Therefore, the author tries to understand and conduct a legal analysis of grain sales with a drop-ship system in Madiun. In this case, the dropship perpetrator did not pay off the grain purchase payment to the supplier, and the perpetrator ran away. Meanwhile, the buyers have paid off the fee for grain purchases to dropship actors. This study aims to determine the dropship system for grain sales in Madiun as well as preventive actions from the Madiun Police against the sale and purchase of grain dropship system in Madiun and analyse cases of fraud and embezzlement of the grain dropship system with PN Decision Study: No 128/Pid.B/2022/PN Mjy. This research is included in normative legal research type research, with research legal sources obtained from the 1945 Constitution, Criminal Code, legal research reports and so on. Based on the results of the study, it can be concluded that the existing grain dropship buying and selling system in the city of Madiun still needs to be improved in this system. Moreover, there needs to be further law enforcement related to selling dropship system grain.